2008
DOI: 10.1002/path.2405
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor gene (ESR1) amplification is frequent in endometrial carcinoma and its precursor lesions

Abstract: Oestrogen receptor alpha (ER) plays a critical, diverse and not fully understood role in endometrial carcinoma. Most endometrial carcinomas express ER and some of these tumours respond favourably to anti-oestrogen therapy. On the other hand, tamoxifen therapy constitutes a major risk factor for endometrial carcinoma development. Amplification of the ESR1 gene encoding ER was recently shown to constitute a mechanism for ER over-expression in breast carcinoma. This study was designed to determine the potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…A closer look at the specific genes that contain somatic insertions reveals several known cancer genes, such as RUNX1, a putative tumor suppressor in gastric carcinoma (Silva et al 2003) that is subject to recurrent loss-of-function inactivation in breast cancer and esophageal adenocarcinoma (Banerji et al 2012;Dulak et al 2012;Koboldt et al 2012), as well as in the exon of REV3L, which has been implicated as a novel tumor suppressor in colorectal and lung cancers, and is involved in maintenance of genomic stability (Brondello et al 2008;Zhang et al 2013). One UCEC sample contains an intronic somatic L1 insertion in the ESR1 gene, an important hormone receptor often overexpressed in endometrial and breast cancers (Lebeau et al 2008). While previous studies found somatic insertion only in intronic regions, we identify 21 somatic events in or within 200 bp of exons of genes such as CYR61 and HSF2, with seven falling in the protein-coding sequence itself ( Fig.…”
Section: Retrotransposons Can Mobilize Into Genic Regionsmentioning
confidence: 59%
“…A closer look at the specific genes that contain somatic insertions reveals several known cancer genes, such as RUNX1, a putative tumor suppressor in gastric carcinoma (Silva et al 2003) that is subject to recurrent loss-of-function inactivation in breast cancer and esophageal adenocarcinoma (Banerji et al 2012;Dulak et al 2012;Koboldt et al 2012), as well as in the exon of REV3L, which has been implicated as a novel tumor suppressor in colorectal and lung cancers, and is involved in maintenance of genomic stability (Brondello et al 2008;Zhang et al 2013). One UCEC sample contains an intronic somatic L1 insertion in the ESR1 gene, an important hormone receptor often overexpressed in endometrial and breast cancers (Lebeau et al 2008). While previous studies found somatic insertion only in intronic regions, we identify 21 somatic events in or within 200 bp of exons of genes such as CYR61 and HSF2, with seven falling in the protein-coding sequence itself ( Fig.…”
Section: Retrotransposons Can Mobilize Into Genic Regionsmentioning
confidence: 59%
“…Recently, p27 has been studied by Horree et al (37) and showed a very heterogeneous expression in EEC. Although the tissue microarray approach has limitations in studying heterogeneous biomarkers, we have recently shown that tissue microarrays can reliably detect genetic alterations in heterogeneous cell populations of endometrial carcinoma (32). In this study, we aimed to determine the direct relationship of PTEN and p27 in welldefined cell populations, which is possible by tissue microarrays.…”
Section: Discussionmentioning
confidence: 99%
“…Selection criteria were based on availability, presence, and size of representative tumor areas in paraffin blocks. Tissue microarrays were constructed as described previously (31,32). Briefly, a tissue arraying instrument (Beecher Instruments) was used to create holes in a recipient paraffin block and to acquire tissue cores from the donor block by a thin-walled needle with an inner diameter of 0.6 mm, held in a X-Y precision guide.…”
Section: Translational Relevancementioning
confidence: 99%
“…Interesting research topics for future studies will be the evaluation of the mechanisms of ESR1 mRNA overexpression, such as ESR1 gene amplification that has been reported in breast and endometrial carcinoma (Holst et al 2007, Lebeau et al 2008. Similarly, progesterone receptor expression might be helpful in the prediction of patient prognosis and therapy response and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%